FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KETIDAKPATUHAN PENDERITA TUBERKULOSIS DALAM BEROBAT DI POLIKLINIK DOTS RSUP SANGLAH DENPASAR - Bagiada, I Made; Putri Primasari, Ni Luh (journal of internal medicine, 2010)
Tuberculosis (TB) is a major public health problem in the world, especially in developing countries such as Indonesia. Itremains a major contributor to the global burden of disease and has received considerable attention in recent years, particularlyin developing countries. In our country, there is a little information about factors that can predict the adherence of TB patients.The objective of this study was to know factors contributing in non-adherence TB patients in polyclinic DOTS RSUP SanglahDenpasar. This study was a cross-sectional descriptive study of 15 adult newly diagnosed TB patients. Patients interviewed withquestionnaires consist of demographic and reasons of their non-adherence for TB treatment. About 12 (80%) of TB patients weremale. We didn?t ! nd much different in knowledge, work, educational status, and home distance among TB patients to in